Exploring Digital Transformation And Entrepreneurial Empowerment As Drivers Of Entrepreneurial Intention In The Halal Industry - Cahyani, Utari Evy; Harahap, Choirunnisa Tri Ana; Nasution, Fitri Yani Lusi Yanti (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This study investigates how digital transformation and entrepreneurial empowerment drive entrepreneurial intention within the halal industry. While research on Muslim youth entrepreneurship has grown, evidence on how digital transformation boosts empowerment and intention in a Sharia-compliant context is limited. The study develops an integrated model combining the TOE framework and TPB to examine the determinants of entrepreneurial intention. Data from 186 Muslim students and young entrepreneurs across Indonesian universities were analyzed using SEM-PLS. Results show digital transformation enhances entrepreneurial empowerment by improving perceived behavioral control, technological readiness, and innovation. Empowerment mediates the effect of digital transformation on entrepreneurial intention, emphasizing digital capabilities' strategic role. The study offers an integrated model linking digital transformation with behavioral and organizational factors, with implications for policymakers and educators to foster digital literacy, ethical innovation, and sustainable halal entrepreneurship.